A smart drug: a pH-responsive photothermal ablation agent for Golgi apparatus activated cancer therapy. Issue 48 (30th May 2017) - Xue, Fengfeng; Wen, Ying; Wei, Peng; Gao, Yilin; Zhou, Zhiguo; Xiao, Shuzhang; Yi, Tao
Abstract : A pH-responsive photothermal ablation agent for Golgi apparatus activated cancer therapy with NIR excitation was developed. Abstract : We report a pH-responsive photothermal ablation agent (pH-PTT ) based on cyanine dyes for photothermal therapy (PTT). The nanoparticles formed by BSA andpH-PTT preferentially accumulated in the Golgi apparatus of cancer cells compared to normal cells, and thus can be specifically activated by the acidic Golgi apparatus in cancer cells for effective PTT both ex vivo and in vivo .